Features of the daily blood pressure in children with diabetes depending on the duration of the disease - G.O. Lezhenko; O.Ye. Pashkova; K.V. Samoylyk (Zaslavsky O.Yu., 2019)
Background. The presence of hypertension, which in diabetic patients occurs 2 times more often than in the general population, increases the risk of cardiovascular complications. The main tool for the diagnosis of hypertension in children is ambulatory blood pressure monitoring (ABPM) due to the fact that a number of ABPM parameters may act as predictors of the development of cardiovascular events. The purpose was to establish the features of the daily blood pressure in children with diabetes depending on the duration of the disease. Materials and methods. The paper investigated the features of the daily arterial pressure in 53 children (mean age 14.79 ± 0.25 years) with diabetes mellitus, according to the ABPM data. Depending on the duration of the disease, there were 3 groups: group 1 - 11 children with disease duration of up to 1 year, group 2 - 19 persons with disease duration of 1-5 years, and group 3 - 23 patients with disease duration of more than 5 years. The control group consisted of 20 children, representative by the age and sex, who had no disorders of carbohydrate metabolism and intercurrent diseases. Results. In children with diabetes, with an increase in the duration of the disease, there was an elevation in the blood pressure, its variability and the index of hypertension. Hypertension occurred in 21.0 % of patients with duration of diabetes from 1 to 5 years and in 43.5 % of persons with disease duration of more than 5 years. Identified changes occurred on the background of the circadian blood pressure changes, which took place during the first year of the disease and observed in 51.0-54.5 % of patients. Among the pathological profiles of nocturnal blood pressure reduction in patients with diabetes mellitus, the non-dipper type prevailed (43.5-47.4 %). Conclusions. The majority of patients with diabetes mellitus experienced changes in blood pressure, the first signs of which were registered in the first year of the disease and progressed with an increase of its the duration. The findings suggest that children with diabetes, regardless of the duration of the disease, should be classified as high risk for developing hypertension.